2017
DOI: 10.1177/1971400917719714
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of normal facial nerve enhancement at 3T MRI using gadobutrol and gadopentetate dimeglumine

Abstract: Background and purpose The facial nerve is unique among cranial nerves in demonstrating normal enhancement of particular segments. The effect of varying T1 relaxivities of gadolinium-based contrast agents on facial nerve enhancement is unclear. In this study, we assess differences in normal facial nerve enhancement with two different gadolinium-based contrast agents, gadobutrol and gadopentetate dimeglumine. In addition, we evaluate differences in facial nerve enhancement with spin-echo (SE) T1 versus 3D inver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
(27 reference statements)
1
2
0
1
Order By: Relevance
“…We consider our study sample to be highly representative for LNB patients due to a prospective study design with a high rate of participation among patients treated in- and outside of hospital, and the proportion of subjects with a definite versus a possible LNB diagnosis is in line with other studies [ 5 , 37 ]. Interobserver agreement of enhancement ratings for the important nerve locations is good, as in several other studies using a similar qualitative visual assessment for nerve enhancement [ 11 , 35 , 38 ]. Generalization of the findings concerning outcome may be limited by the subjects undergoing slightly different treatments, but all subjects received adequate treatment and a previous randomized clinical trial found oral doxycycline to be as efficient as intravenous ceftriaxone [ 23 ].…”
Section: Discussionsupporting
confidence: 70%
“…We consider our study sample to be highly representative for LNB patients due to a prospective study design with a high rate of participation among patients treated in- and outside of hospital, and the proportion of subjects with a definite versus a possible LNB diagnosis is in line with other studies [ 5 , 37 ]. Interobserver agreement of enhancement ratings for the important nerve locations is good, as in several other studies using a similar qualitative visual assessment for nerve enhancement [ 11 , 35 , 38 ]. Generalization of the findings concerning outcome may be limited by the subjects undergoing slightly different treatments, but all subjects received adequate treatment and a previous randomized clinical trial found oral doxycycline to be as efficient as intravenous ceftriaxone [ 23 ].…”
Section: Discussionsupporting
confidence: 70%
“… 15 It could be speculated that differing physicochemical properties of gadolinium based contrast agents (GBCA) such as viscosity, osmolality and longitudinal relaxivity (r1) as well as injected volume may influence the physiological T1 shortening of the facial nerve and its perineural vascular plexus; however, a previous comparison of normal facial nerve enhancement with gadobutrol and gadopentate dimeglumine did not reveal any significant differences. 6 …”
Section: Discussionmentioning
confidence: 99%
“…Signal characteristics and enhancement patterns of each cranial nerve differ as a result of factors such as the presence of the arteriovenous plexus. 22,23 For example, Hong et al. 23 demonstrated that the facial nerve can enhance normally in at least one segment due to the presence of circumneural arteriovenous plexus.…”
Section: Discussionmentioning
confidence: 99%